Effect of upadacitinib on reducing pain in patients with active psoriatic arthritis or ankylosing spondylitis: post hoc analysis of three randomised clinical trials. Issue 1 (24th March 2022) - McInnes, Iain B; Ostor, Andrew J K; Mease, Philip J; Tillett, William; Baraliakos, Xenofon; de Vlam, Kurt; Bessette, Louis; Lippe, Ralph; Maniccia, Anna; Feng, Dai; Gao, Tianming; Zueger, Patrick; et al.
Abstract : Objective: Evaluate the effect of upadacitinib on pain outcomes in patients with active psoriatic arthritis (PsA) or ankylosing spondylitis (AS) across 3 randomised trials (SELECT-PsA 1 and 2 for PsA; SELECT-AXIS 1 for AS). Methods: Patients were randomised to upadacitinib 15 mg once daily or placebo (all 3 studies), or adalimumab 40 mg every other week (SELECT-PsA 1 only). Pain outcomes included proportion of patients achieving ≥30%, ≥50% and ≥70% reduction from baseline in patient global assessment of pain and other end points. Results: A higher proportion of patients receiving upadacitinib versus placebo achieved ≥30%, ≥50% and ≥70% reduction in pain end points as early as week 2; these improvements with upadacitinib were generally sustained or increased through year 1 (PsA 1/2 studies: 64%/48%, 58%/42% and 38%/22%, respectively; SELECT-AXIS 1 study: 76%, 72% and 54%). Results were similar with adalimumab in PsA 1 (59%, 49% and 32%). Patients who switched from placebo to upadacitinib 15 mg were able to reach a similar level of improvement as the continuous upadacitinib groups by year 1 (PsA 1/2 studies: 46%–60%, 35%–49% and 15%–34%; AS study: 83%, 72% and 46%). Results were similar with other pain end points. Conclusion: Rapid and sustained improvements in pain outcomes across several end points were consistently shown with upadacitinib over 1 year in patients with active PsA or AS who had either inadequate response to prior non-biologic or biologic disease-modifying antirheumatic drugs (PsA studies) or were biologic-naïve with inadequate response to non-steroidal anti-inflammatory drugs (AS study).